Microfungi associated with Clematis (Ranunculaceae) with an integrated approach to delimiting species boundaries - Chayanard Phukhamsakda (2020)
© 2020, The Author(s). The cosmopolitan plant genus Clematis contains many climbing species that can be found worldwide. The genus occurs in the wild and is grown commercially for horticulture. Microfungi on Clematis were collected from Belgium, China, Italy, Thailand and the UK. They are characterized by morphology and analyses of gene sequence data using an integrated species concept to validate identifications. The study revealed two new families, 12 new genera, 50 new species, 26 new host records with one dimorphic character report, and ten species are transferred to other genera. The new families revealed by multigene phylogeny are Longiostiolaceae and Pseudomassarinaceae in Pleosporales (Dothideomycetes). New genera are Anthodidymella (Didymellaceae), Anthosulcatispora and Parasulcatispora (Sulcatisporaceae), Fusiformispora (Amniculicolaceae), Longispora (Phaeosphaeriaceae), Neobyssosphaeria (Melanommataceae), Neoleptosporella (Chaetosphaeriales, genera incertae sedis), Neostictis (Stictidaceae), Pseudohelminthosporium (Neomassarinaceae), Pseudomassarina (Pseudomassarinaceae), Sclerenchymomyces (Leptosphaeriaceae) and Xenoplectosphaerella (Plectosphaerellaceae). The newly described species are Alloleptosphaeria clematidis, Anthodidymella ranunculacearum, Anthosulcatispora subglobosa, Aquadictyospora clematidis, Brunneofusispora clematidis, Chaetosphaeronema clematidicola, C. clematidis, Chromolaenicola clematidis, Diaporthe clematidina, Dictyocheirospora clematidis, Distoseptispora clematidis, Floricola clematidis, Fusiformispora clematidis, Hermatomyces clematidis, Leptospora clematidis, Longispora clematidis, Massariosphaeria clematidis, Melomastia clematidis, M. fulvicomae, Neobyssosphaeria clematidis, Neoleptosporella clematidis, Neoroussoella clematidis, N. fulvicomae, Neostictis nigricans, Neovaginatispora clematidis, Parasulcatispora clematidis, Parathyridaria clematidis, P. serratifoliae, P. virginianae, Periconia verrucose, Phomatospora uniseriata, Pleopunctum clematidis, Pseudocapulatispora clematidis, Pseudocoleophoma clematidis, Pseudohelminthosporium clematidis, Pseudolophiostoma chiangraiense, P. clematidis, Pseudomassarina clematidis, Ramusculicola clematidis, Sarocladium clematidis, Sclerenchymomyces clematidis, Sigarispora clematidicola, S. clematidis, S. montanae, Sordaria clematidis, Stemphylium clematidis, Wojnowiciella clematidis, Xenodidymella clematidis, Xenomassariosphaeria clematidis and Xenoplectosphaerella clematidis. The following fungi are recorded on Clematis species for the first time: Angustimassarina rosarum, Dendryphion europaeum, Dermatiopleospora mariae, Diaporthe ravennica, D. rudis, Dichotomopilus ramosissimum, Dictyocheirospora xishuangbannaensis, Didymosphaeria rubi-ulmifolii, Fitzroyomyces cyperacearum, Fusarium celtidicola, Leptospora thailandica, Memnoniella oblongispora, Neodidymelliopsis longicolla, Neoeutypella baoshanensis, Neoroussoella heveae, Nigrograna chromolaenae, N. obliqua, Pestalotiopsis verruculosa, Pseudoberkleasmium chiangmaiense, Pseudoophiobolus rosae, Pseudoroussoella chromolaenae, P. elaeicola, Ramusculicola thailandica, Stemphylium vesicarium and Torula chromolaenae. The new combinations are Anthodidymella clematidis (≡ Didymella clematidis), A. vitalbina (≡ Didymella vitalbina), Anthosulcatispora brunnea (≡ Neobambusicola brunnea), Fuscohypha kunmingensis (≡ Plectosphaerella kunmingensis), Magnibotryascoma rubriostiolata (≡ Teichospora rubriostiolata), Pararoussoella mangrovei (≡ Roussoella mangrovei), Pseudoneoconiothyrium euonymi (≡ Roussoella euonymi), Sclerenchymomyces jonesii (≡ Neoleptosphaeria jonesii), Stemphylium rosae (≡ Pleospora rosae), and S. rosae-caninae (≡ Pleospora rosae-caninae). The microfungi on Clematis is distributed in several classes of Ascomycota. The analyses are based on morphological examination of specimens, coupled with phylogenetic sequence data. To the best of our knowledge, the consolidated species concept approach is recommended in validating species.